Assessing the Impact Covid-19 Pandemic on the Educational Development of Secondary School Students - Thomas Achoda Omang; Pius U. Angioha (JINAV: Journal of Information and Visualization, 2021)
The current COVID-19 pandemic affecting nearly all nations of the world have had a profound impact on education. In Nigeria, as the cases of infection continue to increase and the extension of measures to curb the spread of the virus now points to the fact that schools are not physically resuming anytime soon. This study examined the extent to which the COVID-19 pandemic measures have affected the educational developmentof secondary school students in Calabar South Local Government Area of Cross River State, Nigeria. Using the descriptive survey method, data was collected from a sample of 400 samples from a population of 191,630 of Calabar South, Cross River State. The sample size was determined using the Slovin Sample Size Formula. The sample was selected using the stratified, purposive and random sampling technique. the instrument of data collection is a semi-structured questionnaire. Data collected was analyzed using descriptive statistics and Simple Lineal Regression at 0.05 level of significance. Result revealed a significant negative effect of the COVID-19 pandemic measures on the educational development of secondary school students in Calabar South, Cross River State, Nigeria. the study recommends amongst others that the Nigerian government need to copy from other developed nation by partnering with its postal service to deliver worksheets to students in their home especially in low-income families that cannot afford computers.